A comprehensive motion analysis – consequences for high precision image-guided radiotherapy of esophageal cancer patients. (3rd April 2021) - Roos, Catharina T. G.; Faiz, Zohra; Visser, Sabine; Dieters, Margriet; van der Laan, Hans Paul; den Otter, Lydia A.; Plukker, John T. M.; Langendijk, Johannes A.; Knopf, Antje-Christin; Muijs, Christina T.; Sijtsema, Nanna M.
Abstract: Background and purpose: When treating patients for esophageal cancer (EC) with photon or proton radiotherapy (RT), breathing motion of the target and neighboring organs may result in deviations from the planned dose distribution. The aim of this study was to evaluate the magnitude and dosimetric impact of breathing motion. Results were based on comparing weekly 4D computed tomography (4D CT) scans with the planning CT, using the diaphragm as an anatomical landmark for EC. Material and methods: A total of 20 EC patients were included in this study. Diaphragm breathing amplitudes and off-sets (changes in position with respect to the planning CT) were determined from delineated left diaphragm structures in weekly 4D CT-scans. The potential dosimetric impact of respiratory motion was shown in several example patients for photon and proton radiotherapy. Results: Variation in diaphragm amplitudes were relatively small and ranged from 0 to 0.8 cm. However, the measured off-sets were larger, ranging from −2.1 to 1.9 cm. Of the 70 repeat CT-scans, the off-set exceeded the ITV-PTV margin of 0.8 cm during expiration in 4 CT-scans (5.7%) and during inspiration in 13 CT-scans (18.6%). The dosimetric validation revealed under- and overdosages in the VMAT and IMPT plans. Conclusions: Despite relatively constant breathing amplitudes, the variation in the diaphragm position (off-set), and consequently tumor position, was clinically relevant. These motion effects may result in either treatments that miss the target volume, or dose deviations in the form of highly localized over- or underdosed regions.